An Aqueous Metal-Ion Capacitor with Oxidized Carbon Nanotubes and Metallic Zinc Electrodes - Tian, Yuheng; Amal, Rose; Wang, Da-Wei (Frontiers in Energy Research, 2016)
An aqueous metal ion capacitor comprising of a zinc anode, an oxidized carbon nanotubes (oCNTs) cathode and a zinc sulfate electrolyte is reported. Since the shuttling cation is Zn2+, this typical metal ion capacitor is named as zinc-ion capacitor (ZIC). The ZIC integrates the divalent zinc stripping/plating chemistry with the surface-enabled pseudocapacitive cation adsorption/desorption on oCNTs. The surface chemistry and crystallographic structure of oCNTs were extensively characterized by combining X-ray photoelectron spectroscopy, Fourier-transformed infrared spectroscopy, Raman spectroscopy and X-ray powder diffraction. The function of the surface oxygen groups in surface cation storage was elucidated by a series of electrochemical measurement and the surface-enabled ZIC showed better performance than the ZIC with an un-oxidized CNT cathode. The reaction mechanism at the oCNT cathode involves the additional reversible Faradaic process, while the CNTs merely show electric double layer capacitive behavior involving a non-Faradaic process. The aqueous hybrid ZIC comprising the oCNT cathode exhibited a specific capacitance of 20 mF cm-2 (corresponding to 53 F g-1) in the range of 0-1.8 V at 10 mV s-1 and a stable cycling performance up to 5000 cycles.